Ubudiyah Practice Assistance for the Congregation of the Baitus Sholihin Mosque, Sidowaras, Sumbermulyo, Jogoroto, Jombang - Dimyati, Yayat; Luthfi, Ibnu Mas’ud (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2024)
The worship practice orientation program was carried out by the Human Development Cadre Team in Sidorawas Hamlet, Sumbermulyo Village by inviting fostered partners and congregations for the Maghrib prayer at the Baitus Sholihin mosque, Sidorawas hamlet, Sumbermulyo Village, Jogoroto District, Jombang Regency using the lecture and question and answer method. The approach in this service uses the Asset Based Community Development (ABCD) approach. The results of this mentoring research are able to add knowledge to congregations, realize mosque prosperity, create new enthusiasm in carrying out daily worship and create cooperation between parties in building society.